Ethical leadership, self-efficacy and job satisfaction in China: the moderating role of guanxi. Issue 2 (6th March 2017) - Ren, Shuang; Chadee, Doren
Abstract : Purpose: The purpose of this paper is to investigate how employee perceptions of the ethical conduct of their leaders affect their job satisfaction in the context of the workplace in China. The authors posit that guanxi, which is a complex relational phenomenon deeply rooted in Chinese tradition, may act as a substitute for ethical leadership in the Chinese workplace. Design/methodology/approach: A conceptual model which explicitly incorporates guanxi as a moderator in explaining the relationship between ethical leadership and job satisfaction is developed. This model is then tested using data from a sample ( n =388) of professional employees in nine organisations in Beijing, China. Findings: The results show that, as expected, self-efficacy positively and strongly mediates the ethical leadership-job satisfaction relationship. However, guanxi negatively moderates the overall effect of ethical leadership on job satisfaction with the effect being larger in Chinese-owned enterprises compared to foreign-owned enterprises. The findings suggest that employee relationship with their leaders may act as a substitute for ethical leadership in the Chinese workplace. Research limitations/implications: The main question which this research uncovers is whether the Western-based conceptualisation of ethical leadership is applicable in different cultural contexts. The authors' research shows clearly that in the case of China, guanxi plays a substituting role and reduces the effects of ethical leadership on job satisfaction. Future research could investigate the effects of ethical leadership in different cultural contexts. Practical implications: The substituting effect of guanxi on the ethical leadership-job satisfaction relationship suggests that Western firms need to consider culture as an integral contextual factor in explaining employee job satisfaction when they operate in a different cultural context. Originality/value: The explicit consideration of guanxi as an influencing factor of the effects of ethical leadership on job satisfaction in the context of the workplace in China and the testing of this relationship via a moderated-mediation approach is novel.